2021
DOI: 10.1111/jcpt.13551
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the National Centralized Drug Procurement Policy (4 + 7 policy) on the drug expenditures of patients treated in outpatient and emergency departments in a large tertiary level‐A hospital in China: A single centre, interrupted time series

Abstract: Summary What is known and objective Like many countries in the world, China is also facing growing drug expenditures year by year. In particular, the rising cost of prescription drugs has been one of the critical factors leading to the serious burden on health insurance programs. The high cost of prescription drugs not only threatens the health budget but also limits the nation's investment in other public sectors. China implemented the National Centralized Drug Procurement (NCDP) policy, also known as the "4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Our study showed that after the implementation of NCDP, the total expenditures and drug expenditures of hospitalization for lung cancer patients decreased by 14.13 and 20.75%, respectively. This result was consistent with previous studies and it was reasonable because the NCDP policy was expected to reduce pharmaceutical spending and improve the accessibility of medical services (21)(22)(23). The prices of the 25 winning drugs in the first round of NCDP dropped by an average of 52% with the highest drop of 96% (5).…”
Section: Interpretation Of Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…Our study showed that after the implementation of NCDP, the total expenditures and drug expenditures of hospitalization for lung cancer patients decreased by 14.13 and 20.75%, respectively. This result was consistent with previous studies and it was reasonable because the NCDP policy was expected to reduce pharmaceutical spending and improve the accessibility of medical services (21)(22)(23). The prices of the 25 winning drugs in the first round of NCDP dropped by an average of 52% with the highest drop of 96% (5).…”
Section: Interpretation Of Findingssupporting
confidence: 90%
“…Although there is strong consistency between drug purchase data and drug use data (such as prescriptions and claims), it is possible that the policy effects on patients could not be evaluated through procurement records (21,22). Only one study used the hospital information system data, but this study applied an interrupted time series design and estimated the average monthly drug expenditures of patients treated in outpatient and emergency departments (23).…”
Section: Introductionmentioning
confidence: 99%
“…There were few reports in China on the policy of centralised drug procurement, and the reported literature payed more attention to the price changes 18–21. In addition, the effect of the new volume-based centralised drug procurement policy (NVBP policy) on the usage and expenditure of related drugs was less reported 22–30…”
Section: Introductionmentioning
confidence: 99%
“…Among these, centralized drug procurement, as a governance tool aimed at controlling costs and guaranteeing the quality of drugs, was mentioned for the first time at national policy level [ 6 ]. The coverage focuses on drugs with high usage and procurement within the basic health insurance drug catalogue [ 7 ]. This policy aims to obtain preferential drug prices by integrating national market purchases, and is termed national centralized drug volume-based procurement (VBP).…”
Section: Introductionmentioning
confidence: 99%